TRANSDUCTION AND TRANSFORMATION IN TEACHING DESCRIPTIVE TEXTS TO 7TH GRADERS - Rindana Meidianti, - (2024)
Teaching English in the classroom involve various communication interactions using different types of modes. This study specifically focuses on the semiotic modes employed by an EFL teacher in delivering lessons, highlighting the processes of transduction (shifting meaning across different modes) and transformation (shifting meaning within a single mode) under the theory of Bezemer and Kress (2008). This descriptive case study was conducted in a Junior High School in Bandung, with one English teacher as the participant. Data were collected through observation, interviews, and document analysis that included lesson plans, selected textbook content from English for Nusantara, and teaching media. Data from observation was aimed to see how the teacher used the modes within his teaching media and teaching practices. Data from selected textbook content, and content in teaching media were analyzed using Kress and Bezemer (2023) MDA (Multimodal Discourse Analysis) and aims to see the original modes to the transduced/transformed modes. Data from interviews were analyzed using thematic analysis. It was aimed to reveal the teacher's point of view. The study revealed that the teacher conducted transduction and transformation in the designing of the lessons and classroom practices. In the designing section, both transduction and transformation are reflected in changes from lesson plans, selected textbook content, and the teacher's teaching media. Transduction in classroom practices extends from verbal to aural and from verbal to visual. Transformation in classroom practices includes transitioning from images to images and from written text in the textbook to written text in the digital platform. These processes were believed to be beneficial for the teacher in addressing students' difficulties in understanding the lesson. However, in this particular case, the teacher encountered certain challenges in finding equivalent material in the other modes. Keywords: Modes; Multimodality; Transduction; Transformation